Nutrition Quality of the Child Feeds and Child Feeding Practices of Children Aged Between 6 and 24 Months in Marsabit County, 2023 - Chepkorir, Rose; Onyango, Agatha Christine; Masinde, David; Musita, Caroline Patricia (European Scientific Journal, ESJ, 2025)
Child feeding practices are considered one of the determinants of malnutrition in under-fives. Inadequate feeding practice is often a greater factor of malnutrition than lack of food. Globally, 1 in 3 children under five are not obtaining adequate nutrition and thus are not growing well. In ASAL regions of Kenya, the main driver of acute malnutrition is poor dietary intake coupled with inappropriate feeding practices. In Marsabit County, undernutrition prevalence varies in different sub-counties. There are areas where malnutrition is very high whereas other areas are relatively low. In the same setting, however, there are children with good health and nutritional status. Therefore, this study aimed to determine the nutrition quality of the child feeds used among children aged 6 to 24 months in Marsabit County. This study adopted an experimental design for laboratory analysis of the food samples. The snowballing technique was used to select 9 women groups with children aged 6-24 months for participatory assessment of child feeding practices. Focus Group Discussion guides were used to obtain qualitative data. A child food sample collection guide was used during the collection of child feeds for laboratory analysis. Univariate analysis was used to obtain the frequency distribution of nutrition quality of the child feeds. Laboratory analysis results on the nutrient content of child foods indicated high nutrient levels, especially for foods that have gone through fermentation, germination, roasting, drying, and frying processes. The study concludes that the nutritional quality of feeds has a significant effect on child-feeding practices in Marsabit County, Kenya. Based on the findings this study recommends that the Marsabit County government should promote traditional food processing methods, such as fermentation, germination, roasting, drying, and frying, through community nutrition programs to enhance the nutrient content of child foods. These programs should focus on educating mothers and caregivers on how to effectively apply these methods to local foods to improve their nutritional value.